Detection of Trypanosoma cruzi DNA in blood by PCR is associated with Chagas cardiomyopathy and disease severity. (10th February 2015) - Sabino, E. C.; Ribeiro, A. L.; Lee, T. H; Oliveira, C. L.; Carneiro‐Proietti, A. B.; Antunes, A. P.; Menezes, M. M.; Ianni, B. M.; Salemi, V. M.; Nastari, L.; Fernandes, F.; Sachdev, V.; et al.
<x xml:space="preserve">Abstract</x> Background The significance of detection of Trypanosoma cruzi DNA in blood of antibody‐positive patients for risk of development of Chagas heart disease is not well established. The objective of this study was to compare detection of T. cruzi DNA with known clinical and laboratory markers of Chagas cardiomyopathy (CC) severity. Methods This is a case–control study nested within a retrospective cohort developed in Brazil to understand the natural history of Chagas disease. The study enrolled 499 T. cruzi seropositive blood donors (SP‐BD) and 488 frequency matched seronegative control donors (SN‐BD) who had donated between 1996 and 2002, and 101 patients with clinically diagnosed CC. In 2008–2010 all enrolled subjects underwent a health questionnaire, medical examination, electrocardiograms and echocardiograms and polymerase chain reaction (PCR) analyses. A blinded panel of three cardiologists adjudicated the outcome of CC. Trypanosoma cruzi kinetoplast minicircle sequences were amplified by real‐time PCR using an assay with a sensitivity of one parasite per 20 mL of blood. All testing was performed on coded samples. Results Rates of PCR detection of T. cruzi DNA were significantly (P = 0.003) higher in CC patients and SP‐BD diagnosed with CC (79/105 [75.2 %]) compared with SP‐BD without CC (143/279 [51.3%]). The presence of parasitaemia was significantly associated with known markers of disease progression such as QRS and QT interval duration, lower left ventricular ejection fraction, higher left ventricular index mass, and elevated troponin and NTpro‐BNP levels. Conclusion Trypanosoma cruzi PCR positivity is associated with presence and severity of cardiomyopathy, suggesting a direct role of parasite persistence in disease pathogenesis.